Pharmacognostical and Preliminary Phytochemical Screening of Nardostachys jatamansi Dc Rhizome, Achyranthus aspera Linn plant and Trachyspermum ammi Linn fruit - Shah, Vrunda V; Shah, Vipul K; Santani, Devdas D (Journal of Drug Delivery and Therapeutics, 2019)
Nardostachys jatamansi, Achyranthus aspera and Trachyspermum ammi are very important medicinal plants which are traditionally used in many medical conditions. The present study involves Pharmacognosy and preliminary phytochemical investigations of the rhizomes, whole plant and fruit parts of above three plants respectively .This study consist of the morphological and microscopical study of the plant; the phytochemical screening and testing for alkaloids, glycosides, tannins, steroids and flavonoids; TLC study and HPTLC fingerprinting. The parameters from the above were recorded with an objective of drawing an attention on the plant as well as a reference for further scientific investigations. Keywords: Nardostachys jatamansi, Achyranthus aspera, Trachyspermum ammi, Flavanoids,  Microscopical, Pharmacognosy.